PENGEMBANGAN MODEL PEMBELAJARAN JARINGAN SYARAF TIRUAN TIPE SUPERVISED LEARNING SEBAGAI MEDIA PEMBELAJARAN - Haryanto, Haryanto; Khairudin, Moh. (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
ABSTRACT The objective of this research to develop an artificial neural networks type of supervised learning as an instructional media of the intelligent control systems (ICS). This instructional media to facilitate understanding of the containts of the ICS subjects. It is expected to increase the quality of course materials and learning outcomes achievements with the viability of an instructional media. This research including need analysis, design, implementation, testing and feedback analysis of instructional media, also verified the instructional media by experts and users. On the instructional media testing covered construction, debugging process, evaluation and improvement, the validated media refined by experts, after that finalisation and media dessimination. Data collecting consists observation, questionnaires, check lists, and documentations. Quantitative, descriptive and evaluative are used in this analysis. The results consist (1) the description of neural network models type of supervised learning as the instructional media on the subject of ICS. (2) systematic materials for the ICS course, and (3) improving of outcomes quality for student achievement. Keywords: instructional media, neural network, supervised learning